Bioaerosols from composting facilities—a review - Wéry, Nathalie (Frontiers in Cellular and Infection Microbiology, 2014)
Bioaerosols generated at composting plants are released during processes that involve the vigorous movement of material such as shredding, compost pile turning, or compost screening. Such bioaerosols are a cause of concern because of their potential impact on both occupational health and the public living in close proximity to such facilities. The biological hazards potentially associated with bioaerosol emissions from composting activities include fungi, bacteria, endotoxin, and 1-3 β-glucans. There is a major lack of knowledge concerning the dispersal of airborne microorganisms emitted by composting plants as well as the potential exposure of nearby residents. This is due in part to the difficulty of tracing specifically these microorganisms in air. In recent years, molecular tools have been used to develop new tracers which should help in risk assessments. This review summarizes current knowledge of microbial diversity in composting aerosols and of the associated risks to health. It also considers methodologies introduced recently to enhance understanding of bioaerosol dispersal, including new molecular indicators and modeling.